Understanding the organisational context for adverse events in the health services: the role of cultural censorship. Issue 4 (1st December 2001) - Hart, E; Hazelgrove, J
Abstract : This paper responds to the current emphasis on organisational learning in the NHS as a means of improving healthcare systems and making hospitals safer places for patients. Conspiracies of silence have been identified as obstacles to organisational learning, covering error and hampering communication. In this paper we question the usefulness of the term and suggest that "cultural censorship", a concept developed by the anthropologist Robin Sherriff, provides a much needed insight into cultures of silence within the NHS. Drawing on a number of illustrations, but in particular the Ritchie inquiry into the disgraced gynaecologist Rodney Ledward, we show how the defining characteristics of cultural censorship can help us to understand how adverse events get pushed underground, only to flourish in the underside of organisational life.